Studies on the influence of sampling on the levels of dioxins and PCB in fish. (December 2018) - Lüth, Anja; Lahrssen-Wiederholt, Monika; Karl, Horst
Abstract: Beaked redfish ( Sebastes mentella ) and Greenland halibut ( Reinhardtius hippoglossoides ) were collected in waters around Svalbard (Barents Sea) to study the influence of different muscle separation/filleting techniques at small and medium fishes on the dioxin/PCB content. Sampling of both species included preparation techniques such as fillets with or without belly flaps, commercially trimmed fillets and cutting into anterior and posterior cutlets. In case of Greenland halibut also the whole edible muscle part and middle cutlets were studied. All samples analysed were far below the maximum level of 6.5 pg/g wet weight (ww) WHO-PCDD/F-PCB-TEQ and 75 ng/g ww ndl-PCB. Trimmed fillets of beaked redfish had the lowest fat content and the lowest level of dioxins and PCB (1.70%, WHO-PCDD/F-PCB-TEQ = 0.320 pg/g ww). The respective posterior cutlets showed the highest fat content and highest levels of dioxins and PCB (2.66%, WHO-PCDD/F-PCB-TEQ = 0.729 pg/g ww). Levels of dioxins and PCB in Greenland halibut samples were generally higher and ranged between WHO-PCDD/F-PCB-TEQ = 0.784 pg/g ww (fillets without bells flaps, fat content = 8.83%) and WHO-PCDD/F-PCB-TEQ = 2.022 pg/g ww (edible part whole muscle, fat content = 8.62%). The results show a considerable influence of the different sampling methods on the dioxin and PCB levels of the species analysed. Graphical abstract: Highlights: Accumulation of dioxins/PCB in fish varies depending on the analysed body part. Sampling method may contribute decisively towards the analytical outcome. Depending on part of fishes consumed, contribution to exhaustion of TDI varies.